Позитивізм як теоретико-методологічне підґрунтя українського історико педагогічного наративу (друга половина ХІХ − початок ХХ ст.) - Галів, Микола; Haliv, Nikolai (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано вплив позитивістських ідей на історико-педагогічні дослідження в Україні впродовж другої половини ХІХ – початку ХХ ст., зокрема сцієнтизму, натуралізму, визначальності емпірично-індуктивної методики накопичення знань, багатофакторності історичного процесу, лінійно-стадіального суспільного прогресу.The article analyzes the influence of positivism ideas in research history of pedagogic in Ukraine during the second half of XIX – early XX century. Given a general description of the doctrine of positivism (O. Cont, J. St. Mill, H. Spencer et al.). It is shown that its distribution has led to a jump in research work in the field of history of education, because the positivism developed a civilization approach, which is focused on the study of spiritual culture, in particular, education. Explicate the influence of the ideas of scientism, naturalism, exclusivity empirical-inductive methods generate knowledge, multifactorial of historical process, linear stages of social progress in the works of historians of education and educational thought (M. Hrushev¬sky, M. Dragomanov, I. Karbulуtskу, V. Motschulsky, J. Nowicki, J. Shulgin et al.).
The Positivism as Theoretical and Methodological Basis of Ukrainian History of Pedagogical Narrative (the Second Half of XIX – the Beginning of XX Century).
Keywords: позитивізм, сцієнтизм, метод індукції, багатофакторність, суспільний прогрес, ліберальна ідеологія.; positivism, scientism, the method of induction, multifactorial, social progress, liberal ideology.